Implementasi Metode Ummi terhadap Kemampuan Membaca Al-Qur’an pada Peserta Didik di Kelas IV SDIT Ruhama Depok - Rahma, Anisa Maulida; Pesha, Indry Yunizul; Asmahasanah, Salati (Intitut Agama Islam Nasional Laa Roiba Bogor, 2024)
The Qur'an is a guideline for Muslims, so it is very important for Muslims to learn it. However, many students have not been able to read the Qur'an properly and correctly according to tajwid. Therefore, a fun, efficient, and effective method is needed so that they can learn the Qur'an appropriately. This study aims to find out the application of the Ummi Method at SDIT Ruhama, the process of implementing Qur'an learning in the Ummi method and the supporting and inhibiting factors for the application of the Ummi Method. This research uses a descriptive qualitative approach through interviews and documentation. The results of the study show that the application of the Ummi method at SDIT Ruhama runs according to the guidelines of the Ummi Foundation by following seven stages: opening, perception, concept planting, understanding, practice, evaluation, and closing. Learning is carried out classically, with teachers using props and students taking turns reading. Sessions last for 60 minutes every Monday to Friday. The success of this method is supported by adequate facilities, certified teachers, and a teacher-student ratio (1:14). However, obstacles related to facilities and infrastructure are still obstacles that need to be overcome to optimize learning.